The Captured Garden: The Political Ecology of Subsistence under Capitalism. (24th March 2014) - Stoll, Steven
Abstract Household subsistence food production did not disappear under capitalism; instead, it functioned within the circulation of capital. British lords and American mining company managers realized that the same practices that once resulted in autonomy for peasants and mountain-dwelling households could be absorbed, "captured, " to subsidize wages. This article considers the captured garden in two forms. The first resulted in capital accumulation, while the second sustained the unemployed without public assistance. Both appeared in West Virginia between the 1880s and the 1930s. Gardens moved into the coal camps, encouraged and compelled by the companies. During the Great Depression the Roosevelt administration established the Division of Subsistence Homesteads, combining gardens and factory wages as a relief program. Both forms illustrate the paradox of subsistence production under capitalism: A practice that for centuries created no surplus value could be made to do just that; an institution once the stronghold of the household could cause dependency and immiseration.